Multifunctional Nacre-Like Nanocomposite Papers for Electromagnetic Interference Shielding via Heterocyclic Aramid/MXene Template-Assisted In-Situ Polypyrrole Assembly - Xiong, Jinhua; Zhao, Xu; Liu, Zonglin; Chen, He; Yan, Qian; Lian, Huanxin; Chen, Yunxiang; Peng, Qingyu; He, Xiaodong (Nano-Micro Letters, 2024)
Robust, ultra-flexible, and multifunctional MXene-based electromagnetic interference (EMI) shielding nanocomposite films exhibit enormous potential for applications in artificial intelligence, wireless telecommunication, and portable/wearable electronic equipment. In this work, a nacre-inspired multifunctional heterocyclic aramid (HA)/MXene@polypyrrole (PPy) (HMP) nanocomposite paper with large-scale, high strength, super toughness, and excellent tolerance to complex conditions is fabricated through the strategy of HA/MXene hydrogel template-assisted in-situ assembly of PPy. Benefiting from the "brick-and-mortar" layered structure and the strong hydrogen-bonding interactions among MXene, HA, and PPy, the paper exhibits remarkable mechanical performances, including high tensile strength (309.7 MPa), outstanding toughness (57.6 MJ m−3), exceptional foldability, and structural stability against ultrasonication. By using the template effect of HA/MXene to guide the assembly of conductive polymers, the synthesized paper obtains excellent electronic conductivity. More importantly, the highly continuous conductive path enables the nanocomposite paper to achieve a splendid EMI shielding effectiveness (EMI SE) of 54.1 dB at an ultra-thin thickness (25.4 μm) and a high specific EMI SE of 17,204.7 dB cm2 g−1. In addition, the papers also have excellent applications in electromagnetic protection, electro-/photothermal de-icing, thermal therapy, and fire safety. These findings broaden the ideas for developing high-performance and multifunctional MXene-based films with enormous application potential in EMI shielding and thermal management. Highlights: 1 The large-scale, high-strength, super-tough, and multifunctional nacre-like heterocyclic aramid (HA)/MXene@polypyrrole (PPy) (HMP) nanocomposite papers were fabricated using the in-situ assembly of PPy onto the HA/MXene hydrogel template. 2 The "brick-and-mortar" layered structure and abundant hydrogen-bonding interactions among MXene, PPy, and HA respond cooperatively to external stress and effectively increase the mechanical properties of HMP nanocomposite papers. 3 The templating effect from HA/MXene was utilized to guide the assembly of conducting polymers, leading to high electrical conductivity and outstanding electromagnetic interference shielding performance.